Technical islamic vocabulary in Malaysian touristic masjid da’wah pamphlets - Jaramillo, Derrick Fernando; Mat Daud, Nuraihan (IIUM Press, International Islamic University Malaysia, 2017)
Mosques can play a role in overcoming negative perceptions of Islam currently prevalent amongst some socienties by producing printed materials that clarify certain Islamic concepts to clear the misunderstandings they may have regarding the Islamic faith. They can be used to explain the basic tenets of islam. however, a large amount of technical Islamic terms can make the materials incomrehensible to non-experts and those who are familiar with the subject of Islam. The printed materials produced by selected mosques in Kuala Lumpur were analyzed and it was found that there was a high usage of Islamic technical terms in these printed materials. These terms are divided into Arabic language words and English language words. The Arabic technical terms might be familiar to a Muslim but a non-Muslim might have never heard of them before. A more proper elucidation is needed when presenting Islamic concepts in English to non-Muslims, as this constitutes a main contributing factor to the future success of these da'wah projects. the language being used in the reading materials should be simplifies if we wish to create a more effective tool for islamic preaching. The results of the study can also be used by English for Specific purposes practitioners when dealing with religious texts.